Ab-Chicken Sharia Partnership Business Strategy: In the Face of a Global Economic Recession - Kurniawan, Heru; Aziz, Abdul (Universitas Alma Ata, 2023)
The threat of a global recession is the thing that entrepreneurs are most aware of, including AB Chicken. In this study, the authors used a qualitative approach with descriptive analysis methods, and data collection techniques were obtained from direct observations in the field. The results of this study AB Chicken as a food and beverage business made three strategies in dealing with the global recession, namely implementing a sharia business concept with a da'wah-based marketing approach, building religious and humanitarian images, partnerships with a family concept, increasing skilled and religious human resources and expanding urban markets with services delivery (cloud kitchen). The novelty of this research is the propaganda media as a marketing strategy for AB Chicken through Buya Yahya's preaching with the motto